Correlation Between Blood Glucose Levels And Risk Of Non-Hemorrhagic Stroke: Analysis Of A Prospective Cohort Study In An Elderly Population - Williem Alexander Hartanto (Syntax Corporation Indonesia, 2024)
Stroke is one of the main cardiovascular diseases that causes death and disability throughout the world. One of the important risk factors for stroke is hyperglycemia or high blood sugar levels. This study aims to analyze the correlation between blood glucose levels and the risk of non-hemorrhagic stroke in the elderly population. This research utilizes a qualitative approach. The data source used is the scientific literature. The data that has been collected is then analyzed through the process of data reduction, data presentation, and conclusion drawing. The research findings show that there was a significant positive correlation between blood glucose levels and the risk of non-hemorrhagic stroke in the elderly population. Elderly people with high blood glucose levels have a higher risk of non-hemorrhagic stroke compared to elderly people with normal blood glucose levels. Good control of blood glucose levels can be an important strategy to reduce the risk of non-hemorrhagic stroke in the elderly.